G302(P) Red-flags – what do parents perceive?. (24th May 2017) - Warren, S; Gite, A
Abstract : Aims: Effective red-flag communication and advice on re-presentation is essential for ensuring safe discharge from hospital, avoidance of complications and promotion of better patient outcomes. However, the increasing strain on A and E allows little time for patient and parent education, potentially impacting on their ability to memorise and recall red-flag guidance after discharge. This study aimed to analyse whether written communication in addition to verbal advice would improve parental recall of red-flags. Methods: Of 480 patients presenting to the Children's Ambulatory Unit from 6/11/16–5/12/16, 113 were diagnosed with common paediatric conditions and included in this study in two distinct cohorts - 63 patients received only verbal red-flag advice at discharge, while 50 additionally received ethically-approved, trust-wide information leaflets, outlining key red-flags and advice on when to re-seek medical attention. Leaflets were used as a standard to determine red-flags per diagnosis. Parents were telephoned within 2 days of discharge to determine their unaided and aided recall of red-flags, and their confidence in assessing red-flags at home. Results: Patient demographics were similar between the two cohorts. No statistical difference was found in mean unaided recall of red-flags between the leaflet and non-leaflet cohorts (51.8% vs. 43.8%; p=0.08). However, the mean aided recall of red-flags was significantly higher in the leaflet cohort compared with the non-leaflet cohort (74.4% vs. 62%; p=0.03). In the leaflet cohort there was strong positive linear correlation between red-flag burden at discharge and unaided parental recall (spearman r=0.78; range 2–4 red-flags recalled); a finding not observed in the non-leaflet cohort, where recall remained static at 2.5 red-flags despite increasing information burden. There was no correlation between red-flag recall and confidence in red-flag assessment. Conclusion: The addition of written communication at discharge significantly improves parental recall of red-flag guidance and increases memory storage capacity to accommodate increasing information burden. However, half of red-flags remain unable to be recalled without aid, raising concerns over patient safety after discharge. Extra consideration should be given to addressing redflag education before discharge, with follow-up telephone calls a useful tool to ensure safe management of paediatric patients at home.